Validity, reliability, and sensitivity to change of the traditional Chinese Urticaria Control Test (UCT) in Hong Kong - Hugo W.F. Mak, MBBS, MRes(Med); Elaine Lee, MSc; Jane C.Y. Wong, MBBS; Karsten Weller, MD; Marcus Maurer, MD; Philip H. Li, MD (Journal of Allergy and Clinical Immunology: Global, 2024)
Background: Uncontrolled chronic urticaria (CU) can severely affect physical and psychosocial health as well as quality of life. Patient-reported outcome measures are crucial for measuring disease control. The Urticaria Control Test (UCT) is recommended by guidelines to monitor CU and guide clinical management. However, the traditional Chinese version of the UCT has not yet been validated. Objective: We sought to validate the traditional Chinese UCT among Chinese CU patients in Hong Kong. Methods: Patients with CU were enrolled at a Urticaria Centre of Reference and Excellence (aka UCARE) in Hong Kong and completed the traditional Chinese UCT. The internal consistency, test–retest reliability, construct validity, convergent validity, known-group validity, and sensitivity to change of the traditional Chinese UCT were evaluated. Results: We recruited 162 CU patients (80.9% female; age 50 ± 14 years) with a mean (median) ± standard deviation baseline UCT score of 8.8 (8) ± 4.7. Overall, Chinese UCT showed excellent internal consistency (Cronbach α and McDonald ω = 0.948), as well as test–retest reliability (intraclass correlation coefficient = 0.916 [95% confidence interval = 0.866-0.953]). Exploratory factor analysis revealed a unidimensional structure and confirmed its construct validity. Strong correlation between UCT and the 7-day urticaria activity score (UAS7) attested to its convergent validity (ρ = −0.699, P < .001). Its known-group validity was supported by significantly different UCT scores among patient subgroups with different disease activity. The Chinese UCT also demonstrated good sensitivity to change, as reflected by the significant correlation between changes in UCT and UAS7 scores (ρ = 0.491, P < .001). Conclusion: The traditional Chinese UCT is a valid, reliable, and sensitive-to-change instrument among Hong Kong Chinese with CU.